Diabetes Risk Evaluation Using Indian Diabetes Risk Score among Adults of an Urban Slum in Bengaluru, Karnataka - S. Saraswathi; Amita Mukhopadhyay; M. Sumana; Ipsita Debata; Prem Sagar Panda (Current Medical Issues)
Background: Diabetes typically projects the Iceberg phenomenon, with most cases being hidden. The Indian diabetes risk score (IDRS) by the Madras diabetic research foundation is a validated and useful screening tool that identifies high-risk people in primary care settings. The study aimed to assess the risk of type 2 diabetes mellitus among adults in an urban slum in Bengaluru, Karnataka with the Indian diabetic risk score (IDRS). Methodology: A cross-sectional study was carried out in the community involving adults, aged 18 years and above, in the urban field practice area for 3 months. A pretested questionnaire with the IDRS tool was used for data collection. Results: Of 300 participants, 53% were males and 47% were females. The diabetes risk, as per the IDRS scores, was high in 58.2%, moderate in 27.2%, and low in 14.6% of the population. The diabetes risk was associated significantly with gender, age, occupational status, physical activity, abdominal circumference, and family history (P < 0.00001). Conclusion: Screening by the IDRS tool showed that the risk of developing diabetes was moderate to high in the study population.